Soil fertility and fertilizers : (Pearson, 2016)
This book provides a thorough understanding of the biological, chemical, and physical properties affecting soil fertility and plant nutrition. Covering all aspects of nutrient management for profitable crop production, the text pays particular attention to minimizing the environmental impact of soil and fertilizer management. This edition has been substantially revised to reflect rapidly advancing knowledge and technologies in both plant nutrition and nutrient management.